Internal Control and Financial Performance of Accounting Firms in Calamba City - Laroza, Den Mark (Journal of Interdisciplinary Perspectives, 2024)
Internal control implementation in accounting firms ensures the integrity of financial information, safeguards assets, and mitigates risks, promoting operational efficiency and compliance with regulatory standards. The main thrust of this study was to describe and determine the relationship between the level of internal control implementation and the financial performance of accounting firms in Calamba City. This study employed a descriptive correlational design and utilized a simple random sampling technique to select the sample, enabling the researcher to obtain representatives from the population. With the aid of the G-power sample size computation application, this study came up with 80 respondents based on a 0.35 effect size and 95% degrees of confidence. As the primary data collection tool, a validated researcher-made questionnaire was utilized. The data gathered were collected, tallied, analyzed, and interpreted using four-point Likert scales, mean, and Pearson Product-Moment Correlation Coefficient. Based on the results of the study, the internal control of accounting firms in Calamba City was fully implemented, and their financial performance was very high, with a general assessment of 3.43 and it explained that these accounting firms have a definite process and procedures for assessing financial information of the customers to secure and to maintain good financial performance among other competitors in the market. As an output of the study, a proposed action plan based on the COSO framework was proposed to improve the quality of the control environment, risk assessment, information and communication, control activities and monitoring procedures, and improve the financial performance of accounting firms in Calamba City.